Análise da influência do tráfico de drogas nos homicídios dolosos em Manaus - Moreira, Emília Ferraz Carvalho (2014)
The “Analysis of the drug traffic influence over the homicides in Manaus” consists in a study proposal that intends generally to analyze the possible relations between the drug Market and the lethal violence in local scenery. To reach this goal, it was necessary to comprehend the peculiarities of the drug traffic in the region and also the dynamics of the criminal network that prevail in the city. Empirically, to verify the possible relation between drugs and violent deaths in Manaus, police Inquiries of the Homicide and Kidnaping Special Police Department that investigate the murders in 2013 were analyzed. The methodology used consisted in a vast bibliographic revision, in a study of legal procedures established to disfavor the criminal, local, faction members and the collect and analyses of the data over homicides in Manaus. The study conclusion reveal the existence of a complex criminal network at work in the State, with the direct incidence on the region’s homicides, since 40% of the l investigative reports indicate the involvement of the parties with drug traffic. Of this total the main victims are male (97%) and young people between 14 and 34 years of age. The study also concluded that the quantity of apprehension by drug traffic have influenced the homicide rate between 2007 to 2013.